The effect of fermentation time and inoculum amount on total sugar, total acid, total flavonoid, total phenol, and inhibition of alpha-glucosidase activity of red ginger kombucha (Zingiber officinale Roscoe) - Euis Filailla; Hani Mulyani; Yati Maryati; Setyani Budiari (Jurnal Kimia Terapan Indonesia, 2022)
Kombucha contains organic compounds that are beneficial to the body, namely B complex vitamins, organic acids, and other compounds. The manufacture of kombucha apart from tea is the red ginger platn (Zingiber officinaleroscoe). Red ginger kombucha fermentation was carried out for 0-14 days with the addition of 10% and 20% incoculum. The fermentation time and the amount of inoculum affected decreasing the total sugar content and pH value, as well as increasing the total acid content, total flavonoid, total phenol, and the ability to inhibit the activity of the alpha glucosidase enzyme. Total acid content, total flavonoid, total phenol, and inhibition of alpha glucosidase enzyme activity increased to 0.22 mg/ml, 19.62 ppm, and 56.70%. The decrease in total sugar and pH values reached 60.80 mg/ml and 3.42.